2015
DOI: 10.1111/jog.12678
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of native tissue reconstructive vaginal surgery for advanced pelvic organ prolapse at 86 months: Hysterectomy versus hysteropexy

Abstract: SSF plus AC and PC have a low reoperation rate despite a moderate success rate at 7-year follow-up. There was no difference in the adjusted objective, subjective success rates and sexual function between sacrospinous hysteropexy and hysterectomy. The hysterectomy group, however, had fewer bothersome prolapse symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
27
1
Order By: Relevance
“…However, uterine preservation has become more prevalent according to its noninferior outcomes based on current evidence. Shorter operation times, less blood loss, better recovery, and lower complication rates have been reported previously 4,7,15,16 . Hefni et al found comparable recurrence rates and reoperation rates between SSH and SSC 17 .…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, uterine preservation has become more prevalent according to its noninferior outcomes based on current evidence. Shorter operation times, less blood loss, better recovery, and lower complication rates have been reported previously 4,7,15,16 . Hefni et al found comparable recurrence rates and reoperation rates between SSH and SSC 17 .…”
Section: Discussionmentioning
confidence: 87%
“…Hefni et al found comparable recurrence rates and reoperation rates between SSH and SSC 17 . Lo et al also found no difference in the objective cure rate after adjusting for age, parity, and postmenopausal status either 4 . There are some studies comparing SSH with other procedures with concomitant VH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery was considered to be the most effective and durable treatment, which includes autologous tissue repair and synthetic mesh implantation. In general, autologous tissue repair showed good integration within host tissues, a minimal to moderate inflammatory response, and a moderate degree of collagen production and underwent a degree of remodeling over the long term, but a high recurrence rate ( Gigliobianco et al, 2015 ; Lo et al, 2015 ). Polypropylene patches are the most used synthetic meshes in implantation surgery, which offer several advantages including lack of transmission of infectious diseases, ease of availability, sustainable tensile strength, and good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%